Early Post-stroke Activation of Vascular Endothelial Growth Factor Receptor 2 Hinders the Receptor 1-Dependent Neuroprotection Afforded by the Endogenous Ligand - Cárdenas-Rivera, Alfredo; Campero-Romero, Aura N.; Heras-Romero, Yessica; Penagos-Puig, Andrés; Rincón-Heredia, Ruth; Tovar-y-Romo, Luis B. (Frontiers in Cellular Neuroscience, 2019)
Vascular endothelial growth factor (VEGF) has long been connected to the development of tissue lesion following ischemic stroke. Contradictory findings either situate VEGF as a promoter of large infarct volumes or as a potential attenuator of damage due to its well documented neuroprotective capability. The core of this discrepancy mostly lies on the substantial number of pleiotropic functions driven by VEGF. Mechanistically, these effects are activated through several VEGF receptors for which various closely related ligands exist. Here, we tested in an experimental model of stroke how the differential activation of VEGF receptors 1 and 2 would modify functional and histological outcomes in the acute phase post-ischemia. We also assessed whether VEGF-mediated responses would involve the modulation of inflammatory mechanisms and how this trophic factor acted specifically on neuronal receptors. We produced ischemic infarcts in adult rats by transiently occluding the middle cerebral artery and induced the pharmacological inhibition of VEGF receptors by i.c.v. administration of the specific VEGFR2 inhibitor SU1498 and the pan-VEGFR blocker Axitinib. We evaluated the neurological performance of animals at 24 h following stroke and the occurrence of brain infarctions analyzed at the gross metabolic and neuronal viability levels. We also assessed the induction of peripheral pro- and anti-inflammatory cytokines in the cerebrospinal fluid and blood and assessed the polarization of activated microglia. Finally, we studied the direct involvement of cortical neuronal receptors for VEGF with in vitro assays of excitotoxic damage. Preferential VEGFR1 activation by the endogenous ligand promotes neuronal protection and prevents the presentation of large volume infarcts that highly correlate with neurological performance, while the concomitant activation of VEGFR2 reduces this effect, even in the presence of exogenous ligand. This process partially involves the polarization of microglia to the state M2. At the cellular level, neurons also responded better to the preferential activation of VEGFR1 when challenged to N-methyl-D-aspartate-induced excitotoxicity. Endogenous activation of VEGFR2 hinders the neuroprotective mechanisms mediated by the activation of VEGFR1. The selective modulation of these concurrent processes might enable the development of therapeutic approaches that target specific VEGFR1-mediated signaling during the acute phase post-stroke.